Biomarker profiles of coagulopathy and alveolar epithelial injury in acute respiratory distress syndrome with idiopathic/immune-related disease or common direct risk factors - Koyama, Kansuke (Crit Care, 2019)
BACKGROUND: Altered coagulation and alveolar injury are the hallmarks of acute respiratory distress syndrome (ARDS). However, whether the biomarkers that reflect pathophysiology differ depending on the etiology of ARDS has not been examined. This study aimed to investigate the biomarker profiles of coagulopathy and alveolar epithelial injury in two subtypes of ARDS: patients with direct common risk factors (dARDS) and those with idiopathic or immune-related diseases (iARDS), which are classified as “ARDS without common risk factors” based on the Berlin definition. METHODS: This retrospective, observational study included adult patients who were admitted to the intensive care unit (ICU) at a university hospital with a diagnosis of ARDS with no indirect risk factors. Plasma biomarkers (thrombin–antithrombin complex [TAT], plasminogen activator inhibitor [PAI]-1, protein C [PC] activity, procalcitonin [PCT], surfactant protein [SP]-D, and KL-6) were routinely measured during the first 5 days of the patient’s ICU stay. RESULTS: Among 138 eligible patients with ARDS, 51 were excluded based on the exclusion criteria (n = 41) or other causes of ARDS (n = 10). Of the remaining 87 patients, 56 were identified as having dARDS and 31 as having iARDS. Among the iARDS patients, TAT (marker of thrombin generation) and PAI-1 (marker of inhibited fibrinolysis) were increased, and PC activity was above normal. In contrast, PC activity was significantly decreased, and TAT or PAI-1 was present at much higher levels in dARDS compared with iARDS patients. Significant differences were also observed in PCT, SP-D, and KL-6 between patients with dARDS and iARDS. The receiver operating characteristic (ROC) analysis showed that areas under the ROC curve for PC activity, PAI-1, PCT, SP-D, and KL-6 were similarly high for distinguishing between dARDS and iARDS (PC 0.86, P = 0.33; PAI-1 0.89, P = 0.95; PCT 0.89, P = 0.66; and SP-D 0.88, P = 0.16 vs. KL-6 0.90, respectively). CONCLUSIONS: Coagulopathy and alveolar epithelial injury were observed in both patients with dARDS and with iARDS. However, their biomarker profiles were significantly different between the two groups. The different patterns of PAI-1, PC activity, SP-D, and KL-6 may help in differentiating between these ARDS subtypes. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13054-019-2559-6) contains supplementary material, which is available to authorized users.